Soda Taxes and Marketing Conduct - Keller, Kristopher O.; Guyt, Jonne Y.; Grewal, Rajdeep (Journal of Marketing Research, 2024)
Soda taxes are an increasingly popular policy tool that discourages purchases of sugar-sweetened beverages. This study analyzes how emphasis on marketing conduct elements and their effectiveness might change after soda tax introductions. Prior studies on the effect of soda taxes focus on price increases but neglect other relevant marketing conduct tools (i.e., promotional frequency, promotional discount depth, and feature promotion frequency). This study documents the changes to marketing conduct elements and their effectiveness due to the introduction of soda tax across more than 200 retail stores in five markets. Findings related to price changes are consistent with prior literature; in addition, the study reveals a substantial, hitherto overlooked decrease in promotional frequency (−2%), promotional depth (−12%), and feature promotion frequency (−14%) compared with matched control markets, exacerbating the tax's negative sales effect. Introducing a soda tax also considerably influences the marketing conduct's effectiveness, such that consumers become less sensitive to changes in regular price, feature promotions, and the depth of the promotional discount but respond more to the presence of promotions. Importantly, marketing conduct and effectiveness changes do not align (e.g., while consumers become more sensitive to promotion frequency, managers often reduce them), a relevant insight for policy making.